2018
DOI: 10.1007/s40618-018-0831-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum betatrophin with fibroblast growth factor-21 in women with polycystic ovary syndrome

Abstract: Our results indicate that betatrophin levels are increased and associated with LH and FGF-21 levels, but not with insulin resistance, in women with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
2
2
Order By: Relevance
“…Of the metabolic cytokines studied here, we only found that lipocalin-2 concentrations were increased in non-obese women with PCOS compared with female controls. The study of these circulating molecules on PCOS yielded largely discrepant results, not only with our present data, but also among earlier reports [56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71]. Such discrepancies might reflect the heterogeneity and complex nature of PCOS, but also differences among studies in the criteria used to diagnose the syndrome and in the characteristics of the population in terms of the association with obesity and other confounding factors which influence heavily metabolic variables.…”
Section: Discussioncontrasting
confidence: 64%
“…Of the metabolic cytokines studied here, we only found that lipocalin-2 concentrations were increased in non-obese women with PCOS compared with female controls. The study of these circulating molecules on PCOS yielded largely discrepant results, not only with our present data, but also among earlier reports [56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71]. Such discrepancies might reflect the heterogeneity and complex nature of PCOS, but also differences among studies in the criteria used to diagnose the syndrome and in the characteristics of the population in terms of the association with obesity and other confounding factors which influence heavily metabolic variables.…”
Section: Discussioncontrasting
confidence: 64%
“…Many researchers have studied FGF21 in adult PCOS patients because of its observed action in metabolic disturbances and proinflammatory pathways, but none in adolescents. Half of the studies about FGF21 demonstrated no differences between the patients and the controls [62,[68][69][70], while others demonstrated prominent FGF21 concentrations in patients with PCOS [71][72][73][74]. This study did not demonstrate any differences in the concentrations of FGF21 between PCOS patients and healthy controls, but the FGF21 concentrations were significantly higher in patients with PCOS and NAFLD than those with PCOS without NAFLD.…”
Section: Discussioncontrasting
confidence: 50%
“…PCOS is the most common endocrine disorder in the fertile female age group and hyperandrogenism,oligoanovulation, and polycystic ovarian morphology are the main features of disease (1,2). These features are related to future metabolic risks for the patient such as obesity, insulin resistance (IR), glucose intolerance, diabetes and metabolic syndrome (3-5).…”
Section: Introductionmentioning
confidence: 99%